2002
DOI: 10.1152/ajpheart.00475.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia leads to adverse cardiac remodeling in hypertensive rats

Abstract: Hyperhomocysteinemia (Hhe), linked to cardiovascular disease by epidemiological studies, may be an important factor in adverse cardiac remodeling in hypertension. Specifically, convergence of myocardial and vascular alterations promoted by Hhe and hypertension may exacerbate cardiac remodeling and myocardial dysfunction. We studied male spontaneously hypertensive rats fed one of three diets: control, intermediate Hhe inducing, or severe Hhe inducing. After 10 wk of dietary intervention, cardiac function was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 40 publications
5
86
1
2
Order By: Relevance
“…A recent study from Korea confirmed this finding (10 ). In animal experiments from the group of Joseph and Kennedy (11,12 ), chronic intermediate HHcy induced cardiac hypertrophy, pathological remodeling (11,13,14 ), and diastolic as well as systolic dysfunction (11,12 ). These findings provide strong evidence for a causal role of HHcy in the pathogenesis of left ventricular dysfunction.…”
mentioning
confidence: 67%
“…A recent study from Korea confirmed this finding (10 ). In animal experiments from the group of Joseph and Kennedy (11,12 ), chronic intermediate HHcy induced cardiac hypertrophy, pathological remodeling (11,13,14 ), and diastolic as well as systolic dysfunction (11,12 ). These findings provide strong evidence for a causal role of HHcy in the pathogenesis of left ventricular dysfunction.…”
mentioning
confidence: 67%
“…Hyperhomocysteinemia has been identified as a causative factor of cardiac stress and dysfunction in both spontaneous hypertensive and normotensive rats [129,130]. In rats, supplementation of diet with homocysteine for 10 weeks produces hyperhomocysteinemia and consequently ventricular dysfunction with compromised systolic and diastolic function [52,130].…”
Section: Homocysteinementioning
confidence: 99%
“…In rats, supplementation of diet with homocysteine for 10 weeks produces hyperhomocysteinemia and consequently ventricular dysfunction with compromised systolic and diastolic function [52,130]. The main factors involved in the development of HF are oxidative stress and inflammatory mediators [129].…”
Section: Homocysteinementioning
confidence: 99%
“…Our study extends these projects in the analysis of big endothelin (indicator of vascular function and neurohumoral activity) and of homocysteine, cysteine, cysteinylglycine, and glutathione (agents affecting primarily myocardial oxidative stress). These agents are likely to have an impact on the development of myocardial hypertrophy and/or fibrosis 36,37 , two important determinants of LV diastolic dysfunction, and could teoretically contribute to the HFNEF diagnostics. In our study, we demonstrated a significant association of big endothelin, PIIINP, and MMP-2 with the diagnosis of HFNEF.…”
Section: Relationship Of Various Biomarkers and Indicators Of Increasmentioning
confidence: 99%